CHILD-FRIENDLY SCHOOL MANAGEMENT: A MULTIPLE CASE STUDY IN AMBON - Costapina Purimahua; Rudolf Kempa; Paul Arjanto (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
Child-Friendly Schools require systematic management to ensure that children learn in safe, inclusive, participatory, and violence-free environments. This study aims to analyze Child-Friendly School management at SD Xaverius A1 Ambon, SMP Negeri 20 Ambon, and SMK Negeri 6 Ambon. A qualitative approach with a multiple case study design was used. Data were collected through in-depth interviews, observation, document analysis, and supporting questionnaires involving principals, teachers, guidance and counseling teachers, school committees, parents, and students. The data were analyzed using the Miles, Huberman, and Saldana interactive model, supported by cross-case comparison to identify similarities and differences among the three schools. The findings show that Child-Friendly School management has generally been implemented well, but the degree of optimization differs across sites. SD Xaverius A1 Ambon showed the most optimal implementation because it had a formal Child-Friendly School decree and more structured programs. SMK Negeri 6 Ambon also showed strong implementation through character development, school-wide coordination, and protection-oriented strategies. SMP Negeri 20 Ambon fulfilled most indicators but still required stronger supervision, student behavior guidance, documentation, and parental involvement. Supporting factors included cooperation among principals, teachers, guidance counselors, committees, parents, and students, while inhibiting factors included peer influence outside school, diverse student characteristics, limited facilities, and uneven parental participation. This study contributes to educational management by showing that Child-Friendly School implementation requires not only formal policy, but also participatory management, consistent supervision, and contextual adaptation across educational levels.